Wiarygodność dokumentów w polskim prawie karnym - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents an extremely important issue, which is the credibility of documents on the basis of Polish criminal law. The author explains the definition of a document under Article 115 § 14 of the Polish Criminal Code on the background of the concept of document within other related fields, such as criminal procedure law and criminology. The author also points out the essence and importance of the credibility of documents as a generic subject of protection of provisions contained in Chapter XXXIV of the Criminal Code, stressing also the importance of expert handwriting examination in assessing the credibility of documents.
Keywords: dokument; wiarygodność; fałszerstwo; przestępstwo; badanie pisma ręcznego